Validation of Autism Stigma Knowledge - Questionnaire (ASK-Q) for Brazilian Portuguese - Paulo Vítor Schultz; Bárbara Brambila-Manso; Larissa Couto-Rosa; Kérilin Stancine Santos Rocha; Dyego Carlos Souza Anacleto de Araújo; Lorena Rocha Ayres; Genival Araujo dos Santos Júnior (Elsevier, 2024)
Background: Low levels of knowledge among health professionals about autism spectrum disorders (ASD) can impair the care provided to people with autism. In Brazil, there are still no validated instruments that assess the knowledge of pharmacy students and pharmacists regarding ASD. Objective: This study aimed to carry out the cross-cultural adaptation of the Autism Stigma Knowledge Questionnaire (ASK-Q) into Brazilian Portuguese and to evaluate the evidence of content validity. Methods: This study was conducted in two stages, as recommended in the literature. Stage 1 corresponded to cross-cultural adaptation carried out in six phases (translation of the ASK-Q, synthesis of the translations, evaluation by a committee of experts, evaluation by the target audience of pharmacy students and pharmacists, reverse translation, and evaluation by the author of the original instrument). Step 2 corresponds to the assessment of content validity evidence. Results: The instrument presented semantic, idiomatic, conceptual, and cultural equivalences, and the author considered the adaptation adequate. Content validity had an adequate coefficient (0.89). The ASK-Q was cross-culturally adapted to the Brazilian context according to the main theoretical framework. Conclusions: Future studies will be conducted to evaluate other evidence for the validity of the ASK-Q-Brasil. These studies will be fundamental in assessing knowledge about ASD.